2014
DOI: 10.1155/2014/748742
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Intake of Quercetin with a Grain-Based Diet Acutely Lowers Postprandial Plasma Glucose and Lipid Concentrations in Pigs

Abstract: Treatment goals of diabetes mellitus type 2 (DMT2) include glycemic control and reduction of nonglycemic risk factors, for example, dyslipidemia. Quercetin, a plant-derived polyphenol, often discussed for possible antidiabetic effects, was investigated for acute postprandial glucose- and lipid-lowering effects in healthy growing pigs. Male pigs (n = 16, body weight = BW 25–30 kg) were fed flavonoid-poor grain-based meals without (GBM) or with quercetin (GBMQ). In a first experiment, postprandial plasma concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
(46 reference statements)
1
6
1
Order By: Relevance
“…In previous studies, Q lowered concentrations of plasma lipids (Hoek-van den Hil et al, 2013;Jung et al, 2013;Wein and Wolffram, 2014), which was explained by the upregulation of genes involved in β-and Ω-FA oxidation and by the downregulation of ketogenic genes (Kobayashi et al, 2010). However, in contrast to our hypothesis, the Q treatment did not improve metabolic status compared with that of the control cows.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…In previous studies, Q lowered concentrations of plasma lipids (Hoek-van den Hil et al, 2013;Jung et al, 2013;Wein and Wolffram, 2014), which was explained by the upregulation of genes involved in β-and Ω-FA oxidation and by the downregulation of ketogenic genes (Kobayashi et al, 2010). However, in contrast to our hypothesis, the Q treatment did not improve metabolic status compared with that of the control cows.…”
Section: Discussioncontrasting
confidence: 94%
“…Some flavonoids have hepatoprotective potential (Harborne and Williams, 2000), and quercetin (Q) is one of the most potent flavonoids (Ader et al, 2000). Several studies, primarily with rodents and pigs, found decreased plasma lipid levels (Hoek-van den Hil et al, 2013;Jung et al, 2013;Wein and Wolffram, 2014) and prevention or reduction of lipid accumulation in the liver after Q treatment (Aguirre et al, 2011;Beltrán-Debón et al, 2011;Joven et al, 2012). The underlying mechanisms of these effects included an improvement in the Ω-and β-oxidation of FA in the liver and an upregulation of the genes involved in lipid metabolism (Kobayashi et al, 2010;Jung et al, 2013;Hoek-van den Hil et al, 2013).…”
Section: Effects Of a 6-wk Intraduodenal Supplementation With Quercetmentioning
confidence: 99%
“…Moreover, the decrease in fat accumulation was accompanied by a decrease in the concentration of free fatty acids with a concomitant decrease in triglyceride concentrations. Our results were consistent with other studies which indicated that RSV and QRC significantly suppressed the serum NEFA levels; however, in the present study we administer the combination of flavonoids and identified each NEFA, which had not been previously reported [ 19 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, complex enzyme-assisted extraction is a higher-efficiency method to improve the release of the insoluble-bound phenolics and obtain the highest content of quercetin and kaempferol than a single enzyme-assisted extraction. As we all know, the absorption efficiency in human intestines and the bioactivities of quercetin were much higher than with its glycoside derivatives [ 21 , 22 , 23 ]. Treatment with β -glucosidase, cellulase, and complex enzymes caused the disruption of the bonds between the phenolics and the cell wall components of the GL matrix; thus, the insoluble-bound phenolics were released into soluble forms ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%